Regulating big business : antitrust in Great Britain and America, 1880-1990 / Tony Freyer. - Freyer, Tony Allan (Cambridge University Press, 1992)
In the late nineteenth century a new form of capitalism emerged in Great Britain and the United States. Before the revolutions in communication and transportation, the owners of firms managed the processes of production, distribution, transportation and communication personally. By the end of the century, however, technological innovation and mass markets fostered the development of large-scale corporate structures, leading to a separation between owners and operators. In this new form of capitalist enterprise managers were increasingly the principal decision makers. This economic transformation spawned social and political tensions which compelled the public and policy makers to decide upon an appropriate response to big business. A primary focus of public discourse was antitrust. This book explores the development of big business and the antitrust response in a comparative context.